Lingkungan Kerja Pada Dinas Pengendalian Penduduk Dan Keluarga Berencana Karawang - Pramana Purbayaksa; Puji Isyanto; Dini Yani (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
The Office of Population and Family Planning Control (DPPKB) Karawang district is a government agency that has an important role in controlling the population in Karawang district through the family planning (KB) program. Practical Work is carried out by means of an internship in an agency or company in the Karawang area related to the aim of providing insight to students about the real world of work. This practical work report aims to find out the Work Environment at the Karawang Population Control and Family Planning Office. The basic method of obtaining data is by means of direct interviews, observations, and direct field observations. Overall the work environment at the Population Control and Family Planning Office in Karawang is running well, comfortably and smoothly, but the problems that often occur in the population control and family planning services are that there are often obstacles to the attendance application, namely SIAP which often occurs errors and makes it difficult for employees, besides that in the work environment of the Karawang Population Control and Family Planning Service there are several people who are not harmonious in carrying out their work. The solution that must be done is to add an internet connection to make it faster and provide training for this SIAP application, while to overcome The solution for workers who are not in harmony is to negotiate and bring someone together in an amicable way so that they are back in harmony again.